The Influence of Additional Red Spinach Flour (Amaranthus hypocondriacus) In Made Feed of Color Quality to Goldfish. - Ramadoni Saputra; Mulyadi '; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study was conducted from 1st of April to 10th May 2017. The research to do cultivation technology faculty of fisheries and marine University of Riau, Pekanbaru. The aim of the research is to know about the dose of additional red spinach flour in made feed that aims to enhance color quality to goldfish. This research used experimental method completely randomized design, with 5 level of treatments and 3 replications. The addition were given by P0 pelet FF-999 (control), P1(red spinach flour 2%), P2(red spinach flour 3%), P3 (red spinach flour 4%), P4 (red spinach flour 5%). Maintenance container that used of 60x40x40 cm, aquarium size with water volume of 60 liter with recirculation system. The used of fish as many as 15 tails/basin. The given of food to fish of 3 replication with ad satiation. The measurement of fish color with the growth of sampling done at the beginning, middle, and at the end. Whereas to success of life calculated in begin and ending researd. Parameter of water quality the measured temperature pH, DO, ammonia of measured begin and at the end. The result research showed that the additional red spinach flour in the feed the given influence to the color of change of godfish with 9,81 color gradiation. 2,51 cm absolute length accretion, 6,29 gram absolute weight accretion, the best of succer of life to treatment P2 and P4 of 100%.Keywords: goldfish, change of color, growth of fish, maintenance